Pengaruh Pendapatan E-Banking dan Pembiayaan Bagi Hasil terhadap Profitabilitas Bank Syariah - Farida Ayu Nusantari (Universitas Budi Luhur, 2026)
The purpose of this study is to analyze the effect of revenue and fund distribution on profitability using the Return on Assets indicator. The research method used is quantitative with an associative nature, utilizing secondary data, namely the 2021-2025 quarterly financial reports of several banks, including Bank Syariah Indonesia, Bank BCA Syariah, and Bank Muamalat. The data used were sourced from company financial reports obtained from the Indonesia Stock Exchange and the official websites of Islamic banks. The results of this study demonstrate that e-banking revenue has a positive and significant effect on ROA, and profit-sharing financing also has a positive and significant effect. These findings indicate that optimizing digital-based services with e-banking connected through profit-sharing financing can improve the financial performance of Islamic banks. The novelty of this study lies in the integration of banking digitalization variables with the specific characteristics of profit-sharing financing into a single actual model with the latest quarterly data. Suggestions for further research include adding other variables such as financing risk, liquidity, and operational efficiency. Furthermore, more comprehensive methods could be used, such as panel data regression and other econometric methods.